LAPORAN PRAKTEK KERJA LAPANGAN SEBAGAI PRAMUWISATA BAHASA JEPANG DI CANDI BOROBUDUR - , CALLISTA CHRISTINE SUSILO, Stedi Wardoyo, S.S, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The final project titled âReport of Field Work Practice as a Japanesse Guide at Borobudur Templeâ. Activities undertaken during the field work is the introduction of environmental, escort, hunting, delivery of materials and exams. Constraint experienced during field work activities is there was no definite timetable for the delivery of content. The subject was also not accompanied by a syllabus or handout so that participants do not know what materials that will be provided. In addition, the escort schedules for participants was not clearly divided. These constraints make the author choose the theme of field work as a final project. The purpose of writing this thesis is to evaluate the implementation of the field work activities at Borobudur Temple in hope that the implementation will be more organized in the future. The author uses qualitative methods of data collection through interviews and charging questionnaires. It can be concluded that there are advantages and disadvantages in the implementation of field work activities in Borobudur Temple. The advantages of field work activites are participant gain experience, gain knowledge about the temple, adding Japanese vocabulary, etc. While the disadvantage from field work activites undertaken during one month in Borobudur Temple is that activities was not well organized.